2015
DOI: 10.1007/s12282-015-0653-4
|View full text |Cite
|
Sign up to set email alerts
|

Immunohistochemical analyses of CD44 variant isoforms in invasive micropapillary carcinoma of the breast: comparison with a concurrent conventional invasive carcinoma of no special type component

Abstract: Decreased CD44 expression may play an important role in promoting lymph node metastasis in IMPC through an inability or decreased capacity to bind with the surrounding stroma. Moreover, high CD44s expression levels in the concurrent ICNST component may be related to the development of IMPC.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
19
1
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 19 publications
(22 citation statements)
references
References 24 publications
1
19
1
1
Order By: Relevance
“…This was a higher frequency than that reported by others (about 2%) [11][12][13]. Despite our small number of cases (n=29), the 3-year and subsequent cumulative disease-free survival rates plateaued at 58.8%, and the 6-year and subsequent cumulative survival rates plateaued at 60.8%.…”
Section: Discussioncontrasting
confidence: 57%
“…This was a higher frequency than that reported by others (about 2%) [11][12][13]. Despite our small number of cases (n=29), the 3-year and subsequent cumulative disease-free survival rates plateaued at 58.8%, and the 6-year and subsequent cumulative survival rates plateaued at 60.8%.…”
Section: Discussioncontrasting
confidence: 57%
“…[ 15 ] In contrast, it can express in a variety of breast cancer. [ 15 17 ] However, this had no reports of the CD44v expression in myoepithelial and squamous differentiation of LGASC previously. Furthermore, CD44v, a widely accepted cancer stem cell (CSC) marker in breast cancer, is considered to promote the tumor progression in various cancers.…”
Section: Discussionmentioning
confidence: 98%
“…55 Li et al 51 demonstrated that the ratio of CD44 þ to CD24 À/low tumor cells was higher in IMPCs than it was in IDC-NOS, and the increased CD44 þ to CD24 À/low ratio was associated with more-frequent metastasis of IMPC and a worse prognosis. Umeda et al 56 reported that downregulation of CD44v6, a CD44 variant isoform, was specifically associated with LNM of IMPCs. Interestingly, Badyal et al 37 reported 7 cases of IMPC that regained CD44 expression at the LNM site and hypothesized that its reexpression at the metastatic site had a role in the homing of tumor cells.…”
Section: Mechanism Of Metastasismentioning
confidence: 99%